2023
DOI: 10.1186/s12903-023-02906-2
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of integrating oral health care within universal health coverage and general health care in low-, middle-, and high-income countries: a scoping review

Abstract: Background The World Health Organization (WHO) has recently devoted special attention to oral health and oral health care recommending the latter becoming part of universal health coverage (UHC) so as to reduce oral health inequalities across the globe. In this context, as countries consider acting on this recommendation, it is essential to develop a monitoring framework to measure the progress of integrating oral health/health care into UHC. This study aimed to identify existing measures in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 99 publications
0
1
0
Order By: Relevance
“…Yet neither these initiatives or their documents define what is an essential oral health service or the set of criteria to be used in defining those. In addition, a framework on how to define an essential benefits basket is still lacking (Jashni et al, 2023). A systematic review found that having an OH benefits package is a precondition to integrate OH into primary care (Christian et al, 2023), but it does not specify how to set or define this package.…”
Section: Introductionmentioning
confidence: 99%
“…Yet neither these initiatives or their documents define what is an essential oral health service or the set of criteria to be used in defining those. In addition, a framework on how to define an essential benefits basket is still lacking (Jashni et al, 2023). A systematic review found that having an OH benefits package is a precondition to integrate OH into primary care (Christian et al, 2023), but it does not specify how to set or define this package.…”
Section: Introductionmentioning
confidence: 99%